Applying maximum entropy to econometric problems - Hill, R. Carter; Fomby, Thomas B. (Emerald, 1997)
The entropy concept was developed and used by Shannon in 1940 as a measure of uncertainty in the context of information theory. In 1957 Jaynes made use of Shannon's entropy concept as a basis for estimation and inference in problems that are ill-suited for traditional statistical procedures. This volume consists of two sections. The first section contains papers developing econometric methods based on the entropy principle. An interesting array of applications is presented in the second section of the volume.
Keywords: Business & Economics -- Econometrics.; Science -- History.; Econometrics.; elektronické knihy; electronic books